Compendia of world's medicinal flora - Singh, A. P. 1971- (Science Publishers, 2006)
Alternative systems of medicine (Ayurveda, Siddha, Homoepathy, Traditional Chinese Medicine and Western Medcila Herbalism) utilizes medicinal plants for formulations. The present work is aimed at documentation of chemical composition, medicinal use and modern investigative work on medicinal plants. As the name of the title suggests, the work includes rare medicinal plants used globally in medicine. As research is being done on medicinal plants, more and more phytochemicals are being discovered. On basis of this, traditional uses of medicinal plants are being confirmed. The work will be a valuable guide for practitioners of alternative systems of medicine. It will be useful for phytochemists, ethnobotanists and herbal pharmacists who will find unique data about less documented medicinal plants.